Encyclopedia of Analytical Chemistry 2014
DOI: 10.1002/9780470027318.a1625.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Peptide Diastereomers

Abstract: Diastereomeric peptides, isomers in which one or more of the chiral centers have been converted to the opposite configuration (R or S, D or L ), often possess different biological activities and/or conformational properties. Therefore, the separation and determination of diastereomeric peptides is important in life sciences and particularly significant to the pharmaceutical industry for quality control of peptide synthesis and stability as well as for regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 156 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…After optimization studies using several nonchiral hydrogenation catalysts, we found that the hydrogenation using Pd­(OH) 2 /C in 0.4 N HCl in CPME/AcOH (1:9) proceeded smoothly to afford 11n in 90% yield with 65:35 dr. When diastereoselectivity is not sufficiently high, separation of these diastereomers is usually carried out by recrystallization, including chiral resolution, chiral derivatization, or the use of HPLC technology, and we accomplished the separation of these diastereomers to obtain highly pure 11f , 11h , 11i , and 11l – 11n by practical techniques of recrystallization and/or normal phase silica-gel column chromatography without any chiral sources . All spectroscopic data pertaining to the produced di- and tripeptides 11a – 11q were accorded with those of the authentic samples prepared via a common synthetic method using 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide hydrochloride (WSC·HCl) and 1-hydroxybenzotriazole (HOBt)…”
Section: Resultsmentioning
confidence: 99%
“…After optimization studies using several nonchiral hydrogenation catalysts, we found that the hydrogenation using Pd­(OH) 2 /C in 0.4 N HCl in CPME/AcOH (1:9) proceeded smoothly to afford 11n in 90% yield with 65:35 dr. When diastereoselectivity is not sufficiently high, separation of these diastereomers is usually carried out by recrystallization, including chiral resolution, chiral derivatization, or the use of HPLC technology, and we accomplished the separation of these diastereomers to obtain highly pure 11f , 11h , 11i , and 11l – 11n by practical techniques of recrystallization and/or normal phase silica-gel column chromatography without any chiral sources . All spectroscopic data pertaining to the produced di- and tripeptides 11a – 11q were accorded with those of the authentic samples prepared via a common synthetic method using 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide hydrochloride (WSC·HCl) and 1-hydroxybenzotriazole (HOBt)…”
Section: Resultsmentioning
confidence: 99%